Constructing optimal experience for the hospitalized newborn through neuro-based music therapy - Shoemark, Helen; Hanson-Abromeit, Deanna; Stewart, Lauren (Frontiers in Human Neuroscience, 2015)
Music-based intervention for hospitalized newborn infants has traditionally been based in a biomedical model, with physiological stability as the prime objective. More recent applications are grounded in other theories, including attachment, trauma and neurological models in which infant, parent and the dyadic interaction may be viewed as a dynamic system bound by the common context of the NICU. The immature state of the preterm infant’s neurological system and particularly auditory system means that no assumptions can be made about auditory processing and stimulation should proceed with caution. The infant’s experience of an unpredictable auditory environment is further compromised by a potential lack of meaningful auditory stimulation. Parents often feel disconnected from their own capacities to nurture their infant. The implications for the infant’s neurobehavioral and psychological well-being are life-long. This perspectives paper will outline the likely neurological considerations for auditory processing in the premature infant as well as establishing a premise for music-based interventions. A hypothetical clinical case will illustrate the application of music by a music therapist with an infant and family in NICU.